Anda di halaman 1dari 4

# Advanced Classical Physics, Autumn 2013 Problem Sheet 9 – Solutions

x0µ = Λµ ν xν ,

so
x00 γx0 − γβx3
   
x01   x1 
 = .
x02   x 2 
x03 0
−γβx + γx 3

## Substituting x0 = ct, x1 = x, x2 = y, x3 = z, and β = u/c, we find

 0  
ct γ(ct − uz/c)
 x0   x 
 = ,
0
y   y 
z 0 γ(z − ut)

i.e., t0 = γ t − uz
, x0 = x, y 0 = y and z 0 = γ (z − ut).

c2
(b)
2
`0 = (x00 )2 − (x01 )2 − (x02 )2 − (x03 )2
= (γx0 − γβx3 )2 − (x1 )2 − (x2 )2 − (−γβx0 + γx3 )2
= γ 2 (x0 )2 − 2γ 2 βx0 x3 + γ 2 β 2 (x3 )2 − (x1 )2 − (x2 )2
−γ 2 β 2 (x0 )2 + 2γ 2 βx0 x3 − γ 2 (x3 )2
= γ 2 (1 − β 2 )(x0 )2 − (x1 )2 − (x2 )2 − γ 2 (1 − β 2 )(x3 )2
= (x0 )2 − (x1 )2 − (x2 )2 − (x3 )2 ,

because γ 2 (1 − β 2 ) = 1.
(c) x0 = ct, x1 = 0, x2 = 0, x3 = z. However, z = ct since photons move at the speed of
light, so xµ = (ct, 0, 0, ct). The squared length of the spacetime displacement 4–vector is
2 2 2 2
`2 = x0 − x1 − x2 − x3 = c2 t2 − c2 t2 = 0 .

So, despite the fact that the components do not vanish, the spacetime displacement of a
photon is a null 4–vector!

2. (a)
ξ 0µ ξµ0 = Λµ ν ξ ν Λµ ρ ξρ = ξ ν Λµ ν Λµ ρ ξρ .
Now swap the summation indices µ → ρ, ρ → ν, ν → µ,

ξ 0µ ξµ0 = ξ µ Λρ µ Λρ ν ξν = ξ µ δµ ν ξν = ξ µ ξµ = `2 .

## Hence `2 is frame independent.

(b) We’ll need to show that Λρ µ gρσ Λσ ν = gµν . In the matrix form, this is equivalent to
T
Λ · g · Λ = g,

1
Advanced Classical Physics, Autumn 2013 Problem Sheet 9 – Solutions

where  
1 0 0 0
0 −1 0 0
g=
0 0 −1 0  ,

0 0 0 −1
and, as given in the question,
√ 
−1 0
2 √ 0
−1 2 0 0
Λ=
 0
.
0 0 1
0 0 −1 0
Calculating explicitly, we obtain
√   √ 
2 √−1 0 0 1 0 0 0 −1 0
2 √ 0
T −1 2 0 0  0 −1
  0 0 −1 2 0 0
Λ ·g·Λ =   
 0 0 0 −1 0 0 −1 0   0 0 0 1
0 0 1 0 0 0 0 −1 0 0 −1 0
√  √ 
2 1
√ 0 0 2 −1 0 0

−1 − 2 0 0 −1 2 0 0
=   0
 
0 0 1  0 0 0 1
0 0 −1 0 0 0 −1 0
√ 
2 1
√ 0 0
−1 − 2 0 0
=   0
 = g,
0 0 1
0 0 −1 0
as required.
The inverse transformation matrix (Λ−1 )µ ν can be found by inverting the given matrix
Λµ ν in the usual way, but because Λµ ν is a Lorentz transformation, the inverse matrix is
also given by
−1 T
Λ = g·Λ ·g
  √  
1 0 0 0 −1 0 0
2 √ 1 0 0 0
0 −1 0 0 −1 2 0 0 0 −1 0 0
 
= 
0 0 −1 0   0

0 0 −1 0 0 −1 0 
0 0 0 −1 0 0 1 0 0 0 0 −1
√  
2 −1√ 0 0 1 0 0 0
−1 − 2 0 0 0 −1 0 0
=   
 0 0 0 1  0 0 −1 0 
0 0 −1 0 0 0 0 −1
√ 
2 √1 0 0
 1 2 0 0
=  .
 0 0 0 −1
0 0 1 0
(c) Just as in part (a),
x0µ yµ0 = Λµ ν xν Λµ ρ yρ = xν Λµ ν Λµ ρ yρ = xµ Λρ µ Λρ ν yν = xµ δµ ν yν = xµ yµ .

2
Advanced Classical Physics, Autumn 2013 Problem Sheet 9 – Solutions

(d) In the original frame, uµ = (2, 1, 1, 1) and pµ = (300, 299, 0, 0) × 10−27 kg. In the
rocket’s rest frame, the four-velocity of the rocket is obviously u0µ = (1, 0, 0, 0), and
therefore the energy of the cosmic ray can be written as E 0 = u0µ p0µ . However, this is a
scalar product of two four-vectors and therefore Lorentz invariant, which means that
E 0 = u0µ p0µ = uµ pµ = (2 × 300 − 1 × 299) × 10−27 kg = 301 × 10−27 kg
2
= 301 × 10−27 × 3 × 108 /1.61 × 10−19 eV = 16.8 × 1012 eV
= 16.8 TeV.

## 3. (a) It transforms as [2]

0 0 0 0
F µ ν = Λµ µ Λν ν F µν .
(b) Fµν F µν transforms as [1]
0 0 0 0
Fµ0 ν 0 F µ ν = Λµ0 ρ Λν 0 λ Fρλ Λµ µ Λν µ F µν .
0
Using Λµ0 ρ Λµ µ = δ ρ µ , this becomes [1]
0 0
Fµ0 ν 0 F µ ν = δ ρ µ δ λ ν Fρλ F µν = Fµν F µν .
In terms of the components, we have [2]
3
X
µν 00 2
 X ij 2
(F 0i )2 + (F i0 )2 +

Fµν F = (F ) − (F )
i=1 ij
2
= − 2 (Ex2 + Ey2 + Ex2 ) + 2(Bx2 + By2 + Bz2 ) = 2 B2 − E2 /c2 .

c
 
0 1 0 0
−1 0 0 −1 E ik(x3 −x0 )
F µν = 
 0 0 0 0  ce
 .
0 1 0 0

## Because F µν only depends on x0 and x3 , we have ∂1 F µν = ∂2 F µν = 0, whereas

∂0 F µν = −ikF µν , and ∂3 F µν = ikF µν .
For the first equation, we therefore find
∂µ F µν = ∂0 F 0ν + ∂3 F 3ν = −ik(F 0ν − F 3ν ).
Looking at the form of F µν , we find that F 0ν = F 3ν for all ν, so ∂µ F µν = 0 as required.
For the second equation, we first note that if any two indices are equal, say µ = ν, then
we have (no summation)
∂ µ F µρ + ∂ µ F ρµ + ∂ ρ F µµ = ∂ µ F µρ − ∂ µ F µρ = 0
by antisymmetry. Therefore all indices have to be different. Because F 2µ = 0 and there
is ∂2 F µν = 0, the only case to check is when the index values are 0, 1 and 3,
∂ 0 F 13 + ∂ 1 F 30 + ∂ 3 F 01 = ∂ 0 F 13 + ∂ 3 F 01 = ∂0 F 13 − ∂3 F 01 = −ik(F 13 + F 01 ) = 0.
Therefore the second equation is also satisfied.

3
Advanced Classical Physics, Autumn 2013 Problem Sheet 9 – Solutions

 
γ 0 0 −βγ
0 0 1 0 0 
Λµ µ = 

.
 0 0 1 0 
−βγ 0 0 γ

## The boosted Faraday tensor is [1]

  
γ 0 0 −βγ 0 1 0 0
 −1 0 0 −1 ×
0 0  0 1 0 0 
Fµ ν = 
 
 0 0 1 0   0 0 0 0
−βγ 0 0 γ 0 1 0 0
 
γ 0 0 −βγ
 E eik(x3 −x0 ) .
 0 1 0 0 

 0 0 1 0  c
−βγ 0 0 γ
 
0 γ(1 − β) 0 0
−γ(1 − β) 0 −γ(1 − β)
= 
0  E eik(x3 −x0 ) .
 0 0 0 0  c
0 γ(1 − β) 0 0
We also have to boost the coordinates and write
  00   0 0 
γ(x0 + βx3 )

γ 0 0 βγ x
0 0
0  0 1 0 0  x1   x1
xµ = Λµ0µ xµ = 

  0 =  0
,
 0 0 1 0  x2   x2 
30 30 00
βγ 0 0 γ x γ(x + βx )
0 0 0 0 0 0
so x3 − x0 = γ(x3 + βx0 − x0 − βx3 ) = γ(1 − β)(x3 − x0 ), and we obtain the final
expression [1]
 
0 γ(1 − β) 0 0
−γ(1 − β) 0 −γ(1 − β)
0  E eikγ(1−β)(x3 −x0 ) .
0 0 0 0
Fµ ν =  0 0 0 0  c
0 γ(1 − β) 0 0